To the memory of Tamila A. Marysheva (Ukrainian Journal of Ophthalmology, 2026)
Tamila A. Marysheva (Burnasheva) passed away on December, 7, 2016, at the age of 73 after incurable disease. She worked at the Filatov Institute of Eye Diseases and Tissue Therapy as a senior bibliographer from 1972 and as Head of Scientific Library from 1977 to 2010. She dedicated all her life to improvement of institute’s library.Tamila Marysheva was born on December, 1, 1994 in a town of Jalal-Abad, Kyrgyzstan.